A comparative ANSYS-based force analysis of a new horizontal-axis semi-exposed wind turbine. Issue 4 (August 2020) - Seitenov, Daniyar; Mir-Nasiri, N; Ali, Md Hazrat
Renewable energy sources are growing fast. Nowadays, much effort has been made by inventors to devise new and more efficient configurations of wind turbines. This article describes the mechanical design and resultant force dynamic simulation of an innovative horizontal-axis semi-exposed wind turbine structure. The innovation in wind turbine structure includes the flat shape of its blades and their orientation towards the wind that minimizes the axial component of wind force on the shaft bearings. As a result, wind power is fully utilized to generate a useful rotary force that drives the generator rotor. This enhances the efficiency of the turbine as compared to complex shape blades in traditional horizontal-axis wind turbines. The distinctive feature of the system is also an oscillating shield that automatically protects the generator shaft from overspeeding at extreme wind speeds and, therefore, from generating power above its nominal capacity. The overspeeding may even cause physical damage to the generator. The force analysis of the new wind generator has been conducted for various wind conditions by using ANSYS Fluent. The results are compared to a traditional three-blade horizontal wind turbine to prove the ability of the new semi-exposed wind turbine to collect more driving torque on the shaft. The results of the simulation show the efficiency of the system and the advantage of using this system with the overspeed shield protection.